Reskilling and Upskilling Initiatives in the Indian Industrial Sector (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The Indian industrial sector is undergoing rapid transformations propelled by technological advancements, globalization, and shifting market demands. In response to these changes, the imperative for reskilling and upskilling the workforce has gained prominence. This research study critically examines reskilling and upskilling initiatives within the Indian industrial sector, focusing on their effectiveness, key determinants, and impact on workforce adaptability. Employing a case study methodology, the research evaluates government-led skill development programs, industry- academia collaborations, and private sector initiatives. By identifying critical skills in demand across diverse industrial domains, the study sheds light on the dynamic skill landscape shaped by digital transformation. Furthermore, the research explores barriers and facilitators influencing employee participation in skill development programs, with a specific emphasis on gender disparities. In assessing the correlation between reskilling and career advancement, the study provides insights into the tangible outcomes of workforce development initiatives. Additionally, the research evaluates the role of online learning platforms in industrial skill enhancement and proposes policy recommendations to fortify the reskilling ecosystem in India. The findings of this study contribute valuable insights for policymakers, industrial leaders, and educational institutions aiming to align workforce capabilities with the evolving needs of the Indian industrial landscape.